2011
DOI: 10.3109/0886022x.2011.577543
|View full text |Cite
|
Sign up to set email alerts
|

Complete Reversal of Nephrotic Syndrome Secondary to Amyloidosis with Use of Infliximab in a Patient with Inflammatory Bowel Disease and Ankylosing Spondylitis

Abstract: A 30-year-old woman was diagnosed with ulcerative colitis in January 2006. One year later, she presented because of severe back pain and was diagnosed with ankylosing spondylitis (AS). In February 2008, the patient, while still under standard treatment for ulcerative colitis and AS, was admitted because of massive proteinuria and related symptoms. Nephrotic syndrome was observed and renal biopsy revealed amyloid deposits. After treatment with infliximab, nephrotic syndrome disappeared. We aim to present a case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…One retrospective study of 42 patients with AA amyloidosis due to various rheumatic diseases found that after five years, 72.7% of those treated with anti-Interleukin 6 receptor (IL-6) agents were in clinical and laboratory remission compared to 40.7% of those on anti-tumour necrosis factor therapy (TNF) [42]. However, several reports have described the good response to anti-TNF therapy, especially in those with inflammatory bowel disease [37, 43]. For those with severe hepatic disease and often in genetic types, the liver transplant can be a viable option [44-45].…”
Section: Reviewmentioning
confidence: 99%
“…One retrospective study of 42 patients with AA amyloidosis due to various rheumatic diseases found that after five years, 72.7% of those treated with anti-Interleukin 6 receptor (IL-6) agents were in clinical and laboratory remission compared to 40.7% of those on anti-tumour necrosis factor therapy (TNF) [42]. However, several reports have described the good response to anti-TNF therapy, especially in those with inflammatory bowel disease [37, 43]. For those with severe hepatic disease and often in genetic types, the liver transplant can be a viable option [44-45].…”
Section: Reviewmentioning
confidence: 99%
“…In recent years case reports have shown a reduction of proteinuria in patients receiving anti-TGF-β therapy. TNF-α blockade was successfully used to treat nephrotic syndrome in a patient with AA amyloid due to TNF receptor-associated periodic syndrome [112], and complete reversal of nephrotic syndrome secondary to amyloidosis was observed in a patient with inflammatory bowel disease and ankylosing spondylitis after treatment with infliximab (anti-TNF-α antibody) [113]. In a small study with 15 patients with renal amyloidosis, anti-TNF therapy had positive effects on the reduction of proteinuria in some patients [114].…”
Section: Anti-transforming Growth Factor Beta Therapymentioning
confidence: 99%
“…There are several tools for amyloid typing, including immunofluorescence, immunohistochemistry, immunoelectron microscopy, and proteomic studies [14,46]. Unfortunately, amyloid typing was not used in 11 reported cases [3,23–29,32,35,36,38]. We found that AA amyloidosis may be accompanied by other related disorders beside IBD, such as arthropathy or arthritis, which was the most reported disorder [3,22,26,29,34], FMF [3], or other extraintestinal manifestations [3,34].…”
Section: Discussionmentioning
confidence: 99%
“…#1 Crohn's Disease 'Crohn Disease'[Mesh] OR Crohn[tiab] OR Crohns[tiab] OR Crohn's[tiab] 65 650 #2Ulcerative colitis 'colitis, ulcerative'[MeSH Terms] OR ulcerative colitis[Text Word] OR colitis[tiab] OR 'ulcerative colitis'[tiab] 89 040 #3 Inflammatory bowel diseases 'inflammatory bowel diseases'[MeSH Terms] OR 'inflammatory bowel disease'[Text Word] OR 'inflammatory bowel disease'[tiab] 118 237 #4 amyloidosis 'amyloidosis'[MeSH Terms] OR amyloidosis[Text Word] OR 'AA amyloidosis'[tiab] OR 'AA-amyloidosis' [tiab]function[3,22,24,25,[27][28][29]31,34,36,37]; additionally, infliximab contributed to patient stability and prevented the progression of proteinuria or renal injury[3,23,30,34,35]; Unfortunately, infliximab failed in a number of cases, which either led to the progression of proteinuria or renal function[3,26,32,34,36,38].…”
mentioning
confidence: 99%